An Incidentaloma: Primitive Neuroectodermal Tumor of the Thymus - Suzanne M. Smith; Abigail Berniker; Stephen B. Iorfido (Case Reports in Medicine)
After presenting for a routine screening exam, and 57-year-old man was diagnosed with an incidentaloma—a primitive neuroectodermal tumor (PNET) of the thymus. A member of the Ewing sarcoma family of tumors, a PNET is typically regarded as a malignancy of childhood and adolescence, usually occurring in the central nervous system. In the case at hand, our patient had an extremely unusual presentation, given his age and tumor location. Initial presentation is the only predictor for long-term survival. Current treatment recommendations advocate complete surgical resection whenever possible, radiation therapy, and adjuvant versus neoadjuvant chemotherapy.